EXPLORING PERIPHERAL FACTORS IMPACTING SEXUAL DIMROPHISM OF THE BED NUCLEUS OF THE STRIA TERMINALIS - Khalid, Roksana (My University, 2016)
Immune-brain-endocrine communication influences behaviour and contributes to the development of the central nervous system (CNS) in a sexually dimorphic manner. The bed nucleus of the stria terminalis (BST) is a highly sexually dimorphic brain region; in most mammalian species the male BST is larger than the female BST. Previously, our lab has shown that male and female mice lacking T cells due to knock out of the beta (b) and delta (d) chains of the T cell receptor (TCRb-/-d-/-) have reduced anxiety-like behaviour. This was shown with increased time spent in the open arms of the elevated plus maze by TCRb-/-d-/- mice compared to wild type (WT) mice of both sexes. T cell deficient mice also show differences in brain volume compared to WT, including a lack of sexual dimorphism in volume of the BST. The present study explored the impact of T cell deficiency on immune and endocrine factors implicated in sex differences of the CNS. The first analysis was of serum Anti-Müllerian hormone (AMH). AMH is a key determinant of the male phenotype during fetal development. It has also been shown by others to contribute to sexual dimorphic development of the BST. Our postnatal analysis of serum AMH using ELISA demonstrated an age and genotype effect, where a peak in serum AMH levels in WT mice of both sexes was absent in both male and female TCRb-/-d-/- mice at postnatal day (P) 7. These results suggest that T cells have an impact on the endocrine system in early life but the process does not appear to be sexually dimorphic. The present study also explored the impact of TCR knockout on microglia, the resident immune cells of the brain. Other have shown microglia contribute to sexual dimorphic brain development. This contribution occurs through interaction with endocrine factors, making them a key player in the immune-brain-endocrine crosstalk. Using immunohistochemistry and the microglial marker, anti-Iba1, microglia were examined in adult and P7 WT and TCRb-/-d-/ mice. To quantify microglia, soma were traced using AxioVision microscope software, and microglia cell number, perimeter, radius, feret ratio, and area in dorsal and ventral BST were assessed. Our results show sex differences in microglia number in dorsal BST in adult WT mice, where female WT mice had a lower number of microglia compared to WT males, however this difference was absent in TCRb-/-d-/- adult mice. There were no effects on microglia number in the ventral BST and morphology analysis did not reveal any effects in the dorsal or ventral BST. Furthermore, the difference in microglia number was absent in all groups of P7 mice and analysis of soma morphology did not reveal any significant effects. This study explored the impact of TCR knockout on the BST by exploring the immune and endocrine factors shown to contribute to its sexual dimorphic development. The results suggest a non-dimorphic impact on the endocrine system in the postnatal period and a dimorphic impact on microglia that is age and region-specific. The findings reveal a complex network emphasizing the importance of a systems-wide approach to the study of sex differences in the CNS.
Keywords: AMH; Microglia; T lymphocytes; Bed nucleus of the stria terminalis